2010
DOI: 10.4323/rjlm.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features in myocardial bridging

Abstract: Myocardial bridging is a common coronary anomaly characterized by the presence of a muscle bridge above an epicardial artery. Although its involvement in the development of severe cardiovascular pathologies is disputed there are many proofs that it may possibly be associated, in particular circumstances, with sudden cardiac death, the development of malignant arrhythmias, atherosclerosis, myocardial infarction, hibernation or stunning, etc. The development of cardiovascular complications is mainly dependent up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 79 publications
(46 reference statements)
1
13
1
1
Order By: Relevance
“…Various studies suggested that, to have hemodynamic significance, a MB has to have some particular morphological characteristics (especially length and thickness) . Our study showed that a “typical” myocardial bridge has around 19 mm in length and 2.5 mm in thickness, values that can be considered hemodynamically significant .…”
Section: Discussionmentioning
confidence: 49%
“…Various studies suggested that, to have hemodynamic significance, a MB has to have some particular morphological characteristics (especially length and thickness) . Our study showed that a “typical” myocardial bridge has around 19 mm in length and 2.5 mm in thickness, values that can be considered hemodynamically significant .…”
Section: Discussionmentioning
confidence: 49%
“…Marked reduction of the intimal thickness and changes in the endothelial cell morphology of the intima were observed in the tunnelled segment of the coronary branch. These changes might be due to the exposure of intima to a high shear stress [10]. Histologically, the intima of the bridged segment was formed only of contractile--type smooth muscle cells and an abundance of interstitial spiralled collagen, with the absence of the synthetic-type of smooth muscle cells that proliferate and produce the collagen and elastic fibres in the intima as atherosclerosis progresses [2].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the course of AIA and the direction of the overlying myocardial fibres, MB were classified into superficial and deep [10]. The authors added that in superficial MB the AIA passed within the interventricular sulcus and was crossed by the myocardial fibres perpendicular or in acute angle, while in deep form the AIA deviated towards the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dan Dermengiu et.al. (2010) (16) the length of typical myocardial bridge is usually within the 10-30 mm range, only rarely exceeding 40mm. A longer Myocardial Bridges seem to be associated with more significant hemodynamic effect and more sever clinical symptoms Some report attribute the clinical symptoms of myocardial bridges to their extensive length (Kramer et al,1982 (17) , Angelini et al,1983 (14) , Juilliere et al 1995 (18) ).…”
Section: IVmentioning
confidence: 99%